International Alliance of Urolithiasis (IAU) guideline on retrograde intrarenal surgery (Russian adaptation) - Guohua Zeng; Olivier Traxer; Wen Zhong; Palle Osther; Margaret Pearle; Glenn M. Preminger; Giorgio Mazzon; Christian Seitz; Petrisor Geavlete; Christian Fiori; Khurshid R. Ghani; Ben H. Chew; et al. (Вестник урологии)
Introduction. The emergence of new scientiﬁc and clinical evidence on the use of retrograde intrarenal surgery (RIRS) for the management of kidney stones has prompted periodic systematisation, analysis, and evaluation of outcomes to standardise its application and determine future directions for research and development.Objective. To present the Russian adaptation of a guideline on retrograde intrarenal surgery from the International Urolithiasis Alliance guideline series to provide a theoretical basis for urologists performing RIRS.Materials & Methods. A systematic review was conducted on the RIRS-associated publications available in the PubMed database to prepare a set of recommendations during the period from 1 January 1964 until 1 October 2021. The recommendations were evaluated using the GRADE (Grading of Recommendations, Assessment, Development, and Evaluation) system, which classiﬁes, evaluates, develops, and examines recommendations. The modiﬁed Oxford Centre for Evidence-Based Medicine's (OCEBM) system for categorising the level of evidence and relevant comments have been applied to assess the strength of the conclusions.Results. The research team conducted a comprehensive analysis of 36 published clinical guidelines on the following topics: 1. Indications and Contraindications 2. Preoperative Imaging 3. Preoperative Ureteral Stenting 4. Preoperative Medications 5. Perioperative Use of Antibiotics 6. Use of Antithrombotic Therapy 7. Anesthesia Issues 8. Intraoperative Positioning 9. Equipment 10. Complications.Conclusion. A series of recommendations for RIRS, oﬀered here should help provide safe and eﬀective performance of RIRS.